Product Label Perception, Product Quality On Purchasing Decisions Of UMKM Culinary Products Through Trust As An Intervening Variable In Pasuruan City. - Eni Erwantiningsih; Hari Wahyuni (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study aims to analyze the effect of product label perception and product quality on purchasing decisions of UMKM (Micro, Small, and Medium Enterprises) culinary products, with trust acting as an intervening variable in Pasuruan City. The research employs a quantitative approach with a survey method to gather data from culinary product consumers. The study investigates how consumers' perceptions of product labels and the quality of culinary products influence their purchasing decisions. Furthermore, it explores the role of trust in mediating these relationships. The results of this study are expected to provide valuable insights for UMKM businesses in Pasuruan to improve their marketing strategies, product offerings, and customer engagement by focusing on enhancing product labels, product quality, and building trust with consumers.